Magnesium oxide-magnesium titanate composite material as well as preparation method and application thereof
By preparing magnesium oxide-magnesium titanate composite material and cordierite-mullite scr, the problem of poor alkali resistance and corrosion performance of traditional scr is solved, and the life of the scr is improved and environmentally friendly improvement is achieved.
Patent Information
- Application Number
- CN202510593987.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-01
AI Technical Summary
Traditional cordierite-mullite silhouettes have poor resistance to strong alkali corrosion during the synthesis of lithium and sodium ion batteries, low service life, and difficult to deal with waste silhouettes, which pose environmental risks.
The magnesium oxide-magnesium titanate composite material is used in conjunction with cordierite-mullite silhouette to prepare magnesium oxide-magnesium titanate composite material through microwave heating treatment and ball milling to improve its resistance to thermal shock and alkali corrosion.
It significantly improves the alkali-resistant corrosion performance and service life of the silhouette, reduces environmental protection risks, and has a short material preparation cycle and low cost.
Smart Images

Figure CN120413644A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and particularly to a magnesium oxide-magnesium titanate composite material, a preparation method thereof, and an application thereof. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in new energy vehicles and energy storage fields. At the same time, some enterprises have achieved small-batch production and industrial applications of sodium-ion batteries, making it possible to become another secondary battery technology for large-scale commercial applications in addition to lithium-ion batteries. The cathode material is the core key material of lithium and sodium-ion batteries, and its production mainly adopts the high-temperature solid-phase synthesis process. Among them, the sagger is an important high-temperature structural material and is indispensable. When the cathode material is synthesized, the sagger bears strong alkaline raw materials such as LiOH·H2O, Li2CO3, NaOH, and Na2CO3, and needs to repeatedly enter and exit the high-temperature synthesis heat treatment kiln, which has high requirements for the thermal shock resistance, corrosion resistance, and economy of the sagger. Among them, cordierite-mullite saggers are the most widely used.
[0003] As the commonly used cordierite-mullite sagger for sintering cathode materials, it is extremely easy to react with alkalis (Li + / Na + ) to form a large amount of lithium- or sodium-containing aluminosilicates. The volume densities of these new product phases are quite different from those of the original phases, and cracks, delamination, etc. are more likely to occur on the working surface during sudden temperature changes, ultimately leading to failure. The sodium source in the sodium-ion cathode material has high chemical activity and is also prone to react with Al2O3, SiO2, etc. during the heat treatment process to form low-density phases such as sodium metaaluminate, sodium metasilicate, and sodium silicate, accelerating the cracking, spalling, and even damage of the sagger. Especially in the synthesis temperature range of sodium-ion cathode materials, the generated sodium-containing silicates have low melting points and viscosities, and even directly penetrate the bottom of the sagger, causing the loss of sodium-ion cathode materials. The service life does not exceed 10 times, and even fails after 1-2 times. The used saggers are bonded with metal oxides such as cobalt, manganese, and nickel. It is estimated that millions of saggers are used annually (single sagger ~ 5 kg), and the treatment of these large amounts of solid waste is extremely difficult, facing huge environmental protection risks. Therefore, the sagger materials for lithium and sodium-ion battery cathode materials urgently need to solve the problem of improving the service life. The traditional refractory materials and the basic theories and methods for resisting strong alkali erosion cannot break through the bottleneck of cordierite-mullite alkali resistance, and original innovation breakthroughs are urgently needed. Summary of the Invention
[0004] The purpose of the present invention is to provide a magnesium oxide-magnesium titanate composite material, a preparation method thereof, and an application thereof. When the magnesium oxide-magnesium titanate composite material is used in cooperation with a cordierite-mullite sagger, it can improve its strong alkali erosion resistance while ensuring excellent thermal shock resistance, and solve the problems of poor strong alkali erosion resistance and low service life existing in traditional saggers.
[0005] To achieve the above-mentioned invention objectives, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a magnesium oxide-magnesium titanate composite material, comprising the following steps:
[0007] Mix magnesium oxide and titanium oxide by first ball milling, and perform first microwave heating treatment on the obtained mixed powder to obtain magnesium titanate composite powder;
[0008] Mix the magnesium titanate composite powder and magnesite by second ball milling to obtain a composite;
[0009] After pre-pressing and forming the composite into a ceramic green body, perform second microwave heating treatment to obtain a magnesium oxide-magnesium titanate composite material.
[0010] Preferably, the mass ratio of magnesium oxide, titanium oxide and magnesite is 5-10:100-150:15-20.
[0011] Preferably, the conditions for the first ball milling and mixing include: the ball-to-material ratio is 0.5:1-2:1, the rotation speed is 100-300 r / min, and the time is 60-120 min.
[0012] Preferably, the frequency of the first microwave heating treatment is 2.45 GHz or 9.15 GHz, and the output power is 2-15 kW; the conditions for the first microwave heating treatment include: when the temperature ≤ 600 °C, the power increases by 1 kW every 5-10 min; when the temperature > 600 °C, adjust the heating rate to 10-20 °C / min, heat up to 1200-1400 °C, and keep the temperature for 3-5 h.
[0013] Preferably, the conditions for the second ball milling and mixing include: the ball-to-material ratio is 0.5:1-2:1, the rotation speed is 100-300 r / min, and the time is 60-120 min.
[0014] Preferably, the frequency of the second microwave heating treatment is 2.45 GHz or 9.15 GHz, and the output power is 2-15 kW.
[0015] Preferably, the conditions for the second microwave heating treatment include: when the temperature ≤ 600 °C, the power increases by 1 kW every 5-10 min; when the temperature > 600 °C, adjust the heating rate to 10-20 °C / min, heat up to 1200-1400 °C, and keep the temperature for 3-5 h.
[0016] Preferably, both the first microwave heating treatment and the second microwave heating treatment are carried out in a heat-insulating structure; the heat-insulating structure includes an alumina hollow sphere layer, a lightweight mullite sheet layer or a lightweight quartz layer, a polycrystalline mullite fiber cotton layer or an alumina fiber layer, and a lightweight mullite sheet layer or a lightweight quartz layer, which are sequentially stacked from the inside to the outside.
[0017] The present invention provides a magnesium oxide-magnesium titanate composite material prepared by the preparation method described in the above technical solution.
[0018] The present invention provides an application of the magnesium oxide-magnesium titanate composite material described in the above technical solution in the sintering of a battery cathode material. The magnesium oxide-magnesium titanate composite material is used in combination with a cordierite-mullite crucible substrate as a working surface.
[0019] The present invention provides a preparation method of a magnesium oxide-magnesium titanate composite material. Magnesium oxide and titanium oxide are ball-milled and mixed, and then microwave-heated to obtain a magnesium titanate composite powder. The magnesium titanate composite powder is ball-milled and mixed with magnesite aggregate, and further microwave-heated and sintered to generate a magnesium oxide-magnesium titanate composite material. Among them, the addition of large-particle magnesite aggregate can improve the thermal shock resistance of the material (magnesium oxide, as an alkaline refractory material, has excellent alkali erosion resistance). Moreover, during the sintering process, the magnesium oxide component of the magnesite aggregate diffuses into the matrix, forming a ring gap around the magnesite aggregate, which can improve the thermal shock resistance of the material on the premise of its excellent alkali resistance. The present invention uses microwave sintering to prepare a magnesium oxide-magnesium titanate composite material. The obtained composite material has excellent performance, and has the characteristics of easy sintering, excellent strong alkali resistance, and good thermal shock resistance. It can be used for the sintering of cathode materials, and can greatly improve the service life of the materials used for the sintering of cathode materials.
[0020] The method of the present invention is simple to operate, has a short preparation period and low cost.
[0021] The magnesium oxide-magnesium titanate prepared by the present invention contains an MgO-TiO2-based oxide crystal structure. Magnesium oxide is an alkaline material and has alkali penetration resistance. Its firing system (1400 °C) is within the cordierite-mullite sintering window, which highly coincides with the cordierite-mullite sintering temperature and has good interfacial compatibility. Therefore, the sintering mechanisms of the magnesium oxide-magnesium titanate material and cordierite-mullite in the present invention can be optimized to achieve synergy and realize the synergistic improvement of material properties. Using the magnesium oxide-magnesium titanate composite material described in the present invention as a working surface to improve alkali erosion resistance, and using the crucible matrix as cordierite-mullite to ensure thermal shock resistance, the combined use of the magnesium oxide-magnesium titanate composite material and the cordierite-mullite crucible substrate can greatly improve its strong alkali erosion resistance while ensuring excellent thermal shock resistance.
[0022] The magnesium oxide-magnesium titanate material prepared by the present invention shows excellent alkali resistance in the cathode material erosion test. Description of the Drawings
[0023] Figure 1 It is the XRD pattern of the magnesium oxide - magnesium titanate composite material in Example 1;
[0024] Figure 2 It is the SEM image of the magnesium oxide - magnesium titanate composite material in Example 2. Detailed Description of the Invention
[0025] In the present invention, unless otherwise specified, the raw materials or reagents required for preparation are all commercially available products well - known to those skilled in the art.
[0026] The present invention provides a method for preparing a magnesium oxide - magnesium titanate composite material, comprising the following steps:
[0027] Mix magnesium oxide and titanium oxide by first ball - milling, and subject the obtained mixed powder to first microwave heating treatment to obtain a magnesium titanate composite powder;
[0028] Mix the magnesium titanate composite powder and magnesite by second ball - milling to obtain a composite;
[0029] After pre - pressing and forming the composite to obtain a ceramic green body, perform second microwave heating treatment to obtain a magnesium oxide - magnesium titanate composite material.
[0030] In the present invention, magnesium oxide and titanium oxide are first ball - milled and mixed, and the obtained mixed powder is subjected to first microwave heating treatment to obtain a magnesium titanate composite powder.
[0031] In the present invention, the magnesium oxide, titanium oxide, and magnesite are all micron - sized; the particle sizes of the magnesium oxide and titanium oxide are independently preferably 3 - 5 μm; the particle size of the magnesite is preferably 50 - 100 μm.
[0032] In the present invention, the mass ratio of the magnesium oxide, titanium oxide, and magnesite is preferably 5 - 10:100 - 150:15 - 20, more preferably 6 - 9:110 - 140:16 - 19, and even more preferably 7 - 8:120 - 130:17 - 18.
[0033] In the present invention, the conditions for the first ball - milling and mixing preferably include: the ball - to - material ratio is 0.5:1 - 2:1, the rotation speed is 100 - 300 r / min, and the time is 60 - 120 min; the ball - to - material ratio is further preferably 0.8:1 - 1.8:1, and even more preferably 1.2:1 - 1.5:1; the rotation speed is further preferably 150 - 250 r / min, and even more preferably 180 - 200 r / min; the time is further preferably 70 - 110 min, and even more preferably 90 - 100 min.
[0034] After completing the first ball milling and mixing, the present invention preferably screens the obtained material, and the sieve used for screening is preferably a 60-mesh, 70-mesh or 80-mesh sieve.
[0035] The present invention preferably places the mixed powder obtained from the first ball milling and mixing in a heat preservation structure, and together with the heat preservation structure, places it in a microwave resonant cavity. Turn on the microwave source, intermittently adjust the input power from low to high, and record the reflected power. Record the temperature change above 600 °C to perform the first microwave heating treatment.
[0036] In the present invention, the frequency of the first microwave heating treatment is preferably 2.45 GHz or 9.15 GHz, and the output power is preferably 2 - 15 kW, more preferably 4 - 11 kW, and still more preferably 5 - 8 kW.
[0037] The conditions of the first microwave heating treatment preferably include: when the temperature ≤ 600 °C, the power increases by 1 kW every 5 - 10 min; when the temperature > 600 °C, adjust the heating rate to 10 - 20 °C / min, heat up to 1200 - 1400 °C, and keep the temperature for 3 - 5 h. The heating rate is further preferably 12 - 18 °C / min, and still more preferably 15 - 16 °C / min; preferably heat up to 1250 - 1350 °C, and still more preferably 1280 - 1320 °C; the holding time is further preferably 3.5 - 4.5 h, and still more preferably 3.6 - 4 h.
[0038] After obtaining the magnesium titanate composite powder, the present invention performs the second ball milling and mixing of the magnesium titanate composite powder with magnesite to obtain a composite.
[0039] In the present invention, the conditions of the second ball milling and mixing preferably include: the ball-to-material ratio is 0.5:1 - 2:1, the rotation speed is 100 - 300 r / min, and the time is 60 - 120 min; the ball-to-material ratio is further preferably 0.8:1 - 1.8:1, and still more preferably 1.2:1 - 1.5:1; the rotation speed is further preferably 150 - 250 r / min, and still more preferably 180 - 200 r / min; the time is further preferably 70 - 110 min, and still more preferably 90 - 100 min.
[0040] After completing the second ball milling and mixing, the present invention preferably pre-presses and forms the obtained composite to obtain a ceramic green body, places the ceramic green body in a heat preservation structure, and together with the heat preservation structure, places it in a microwave resonant cavity. Turn on the microwave source, intermittently adjust the input power from low to high, and record the reflected power. Record the temperature change above 600 °C to perform the second microwave heating treatment.
[0041] In the present invention, the pressure for pre - pressing is preferably 70 - 100 MPa, more preferably 75 - 95 MPa, and even more preferably 80 - 90 MPa. The present invention has no special limitation on the time for pre - pressing, which can be adjusted according to actual requirements.
[0042] In the present invention, the frequency of the second microwave heating treatment is preferably 2.45 GHz or 9.15 GHz, and the output power is 2 - 15 kW, more preferably 6 - 10 kW, and even more preferably 7 - 9 kW; the conditions of the second microwave heating treatment preferably include: when the temperature ≤ 600 °C, the power increases by 1 kW every 5 - 10 min; when the temperature > 600 °C, the heating rate is adjusted to 10 - 20 °C / min, heated to 1200 - 1400 °C, and the heat - preservation time is 3 - 5 h. The heating rate is further preferably 12 - 18 °C / min, and even more preferably 14 - 16 °C / min; preferably heated to 1250 - 1350 °C, and even more preferably 1280 - 1320 °C; the heat - preservation time is further preferably 3.5 - 4.5 h, and even more preferably 3.6 - 4 h.
[0043] In the present invention, both the first microwave heating treatment and the second microwave heating treatment are carried out in a heat - preservation structure; the heat - preservation structure preferably includes an alumina hollow - sphere layer, a lightweight mullite sheet layer or a lightweight quartz layer, a polycrystalline mullite fiber cotton layer or an alumina fiber layer, and a lightweight mullite sheet layer or a lightweight quartz layer, which are stacked in sequence from the inside to the outside. The present invention has no special limitation on the source, thickness of each layer material in the heat - preservation structure and the specific preparation of the heat - preservation structure, and the heat - preservation structure can be prepared according to the methods well - known in the art.
[0044] In microwave sintering, the heat - preservation structure is used to maintain temperature uniformity, reduce energy consumption, and control the cooling rate.
[0045] In the heat - preservation structure, the innermost layer is an alumina hollow - sphere layer (as a heat - insulation layer), lightweight mullite sheets or lightweight quartz are used as a heat - preservation layer, there is a mullite cover plate with round holes above, and an alumina hollow - sphere brick is padded below, together forming a sample chamber. The next - outer layer is a polycrystalline mullite fiber cotton or alumina fiber as a heat - preservation layer, and the outermost layer is a quadrilateral structure surrounded by lightweight mullite sheets. The above heat - preservation structure is placed in an alumina crucible to make a microwave sintering device.
[0046] In the present invention, the microwave resonator cavity adopts a conventional structure, and through the distribution of the positions of magnetrons, it is ensured that the microwave field strength distribution in the resonator cavity is uniform; an exhaust device and a probe hole for inserting a far - infrared radiation thermometer are provided at the top of the cavity; the infrared thermometer monitors the temperature of the sample in the resonator cavity in real - time, and the temperature range of the infrared thermometer is 600 - 1800 °C.
[0047] In the present invention, after the green body is placed in the heat preservation structure, in order to equalize the temperature and prevent contamination during the sintering process, calcined alumina powder is covered above the green body, and graphite is covered above the alumina powder. The present invention has no special limitation on the calcined alumina powder and graphite used for covering and the covering thickness, and it can be adjusted according to actual needs by using conventional means in the art.
[0048] The present invention provides a magnesium oxide-magnesium titanate composite material prepared by the preparation method described in the above technical solution. The magnesium oxide-magnesium titanate composite material described in the present invention is used in combination with a cordierite-mullite substrate as a working surface. The magnesium oxide-magnesium titanate composite material described in the present invention has excellent alkali resistance, while the cordierite-mullite substrate provides low thermal expansion and thermal shock resistance.
[0049] The present invention preferably composites the magnesium oxide-magnesium titanate composite material with the cordierite-mullite substrate by hot pressing sintering (pressure 20-50 MPa). The present invention has no special limitation on the hot pressing sintering, and it can be compounded according to the sintering parameters well-known in the art.
[0050] The present invention provides the application of the magnesium oxide-magnesium titanate composite material described in the above technical solution in the sintering of battery cathode materials. The present invention has no special limitation on the application method, and it can be applied according to the methods well-known in the art.
[0051] The following describes in detail the technical solutions provided by the present invention with reference to the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] In the following examples, the particle sizes of magnesium oxide and titanium oxide are 3-5 μm; the particle size of magnesite is 50-100 μm.
[0053] In the following examples, the innermost layer of the heat preservation structure is an alumina hollow sphere layer with a thickness of 8 cm, lightweight quartz with a thickness of 10 cm is used as the heat preservation layer, there is a mullite cover plate with round holes above, and an alumina hollow sphere brick with a thickness of 15 cm is padded below to form a sample chamber; the second outermost layer is a polycrystalline mullite fiber cotton with a thickness of 5 cm as the heat preservation layer, and the outermost layer is a quadrilateral structure surrounded by lightweight mullite sheets with a thickness of 5 cm.
[0054] Example 1
[0055] 1) Add 30 g of titanium oxide powder and 1.5 g of magnesium oxide powder into a ball milling tank, use a planetary ball mill for ball milling, the ball-to-material ratio is 2:1, the rotation speed is 300 r / min, the mixing time is 60 min, and the ball-milled powder is passed through a 60-mesh sieve to obtain a mixed powder;
[0056] 2) Place the obtained mixed powder in a heat-insulating structure, and put it together with the heat-insulating structure in a microwave resonator cavity. Turn on the microwave source with a frequency of 2.45 GHz and an output power of 4 kW. Intermittently adjust the input power from low to high. Below 600 °C, the input power uniformly increases by 1 kW every 10 min. After the temperature reaches 600 °C and the measured temperature is displayed, increase the input power according to the heating rate to maintain the heating rate at 10 °C / min. Wait until the temperature rises to 1200 °C and keep it warm for 3 h, then turn off the microwave source to obtain magnesium titanate composite powder;
[0057] 3) Add the obtained magnesium titanate composite powder and 4.5 g of magnesia into a ball milling jar, and ball mill using a planetary ball mill with a ball-to-material ratio of 2:1, a rotation speed of 300 r / min, and a mixing time of 60 min to obtain a mixed powder after ball milling;
[0058] 4) After pre-pressing the above-mentioned mixed powder into a ceramic green body at a pressure of 70 MPa, place the ceramic green body in a heat-insulating structure, and put it together with the heat-insulating structure in a microwave resonator cavity. Turn on the microwave source with a frequency of 9.15 GHz and an output power of 7 kW. Intermittently adjust the input power from low to high. Below 600 °C, the input power uniformly increases by 1 kW every 10 min. After the temperature reaches 600 °C and the measured temperature is displayed, increase the input power according to the heating rate to maintain the heating rate at 10 °C / min. Wait until the temperature rises to 1200 °C, keep it warm for 3 h, then turn off the microwave source to obtain magnesia-magnesium titanate composite material.
[0059] Example 2
[0060] 1) Add 36 g of titanium oxide powder and 2 g of magnesium oxide powder into a ball milling jar, and ball mill using a planetary ball mill with a ball-to-material ratio of 1.5:1, a rotation speed of 100 r / min, and a mixing time of 90 min. Sieve the powder after ball milling through a 60-mesh sieve to obtain a mixed powder;
[0061] 2) Place the obtained mixed powder in a heat-insulating structure, and put it together with the heat-insulating structure in a microwave resonator cavity. Turn on the microwave source with a frequency of 2.45 GHz and an output power of 5 kW. Intermittently adjust the input power from low to high. Below 600 °C, the input power uniformly increases by 1 kW every 10 min. After the temperature reaches 600 °C and the measured temperature is displayed, increase the input power according to the heating rate to maintain the heating rate at 12 °C / min. Wait until the temperature rises to 1250 °C, keep it warm for 3.5 h, then turn off the microwave source to obtain magnesium titanate composite powder;
[0062] 3) Add the obtained magnesium titanate composite powder and 6 g of magnesia into a ball milling jar, and ball mill using a planetary ball mill with a ball-to-material ratio of 1.5:1, a rotation speed of 200 r / min, and a mixing time of 90 min to obtain a mixed powder after ball milling;
[0063] 4) After pre-pressing the above mixed powder at a pressure of 75 MPa to obtain a ceramic green body, place the ceramic green body in a heat-insulating structure, and then place it together with the heat-insulating structure in a microwave resonant cavity. Turn on the microwave source with a frequency of 9.15 GHz and an output power of 9 kW. Intermittently adjust the input power from low to high. Below 600 °C, the input power uniformly increases by 1 kW every 10 min. After the measured temperature shows 600 °C, increase the input power according to the heating rate to maintain the heating rate at 12 °C / min. Wait until the temperature rises to 1250 °C, keep it warm for 3.5 h, and then turn off the microwave source to obtain the magnesium oxide-magnesium titanate composite material.
[0064] Example 3
[0065] 1) Add 40 g of titanium oxide powder and 4 g of magnesium oxide powder into a ball-milling tank, and ball-mill using a planetary ball mill with a ball-to-material ratio of 1.8:1, a rotation speed of 250 r / min, and a mixing time of 100 min. The milled powder is sieved through a 60-mesh sieve to obtain the mixed powder.
[0066] 2) Place the mixed powder in a heat-insulating structure, and then place it together with the heat-insulating structure in a microwave resonant cavity. Turn on the microwave source with a frequency of 9.15 GHz and an output power of 8 kW. Intermittently adjust the input power from low to high. Below 600 °C, the input power uniformly increases by 1 kW every 10 min. After the measured temperature shows 600 °C, increase the input power according to the heating rate to maintain the heating rate at 15 °C / min. Wait until the temperature rises to 1300 °C, keep it warm for 4 h, and then turn off the microwave source to obtain the magnesium titanate composite powder.
[0067] 3) Add the obtained magnesium titanate composite powder and 8 g of magnesite into a ball-milling tank, and ball-mill using a planetary ball mill with a ball-to-material ratio of 1.8:1, a rotation speed of 250 r / min, and a mixing time of 100 min. After ball-milling, the mixed powder is obtained.
[0068] 4) After pre-pressing the above mixed powder at a pressure of 80 MPa to obtain a ceramic green body, place the ceramic green body in a heat-insulating structure, and then place it together with the heat-insulating structure in a microwave resonant cavity. Turn on the microwave source with a frequency of 2.45 GHz and an output power of 10 kW. Intermittently adjust the input power from low to high. Below 600 °C, the input power uniformly increases by 1 kW every 10 min. After the measured temperature shows 600 °C, increase the input power according to the heating rate to maintain the heating rate at 15 °C / min. Wait until the temperature rises to 1300 °C, keep it warm for 4 h, and then turn off the microwave source to obtain the magnesium oxide-magnesium titanate composite material.
[0069] Example 4
[0070] 1) Add 25 g of titanium oxide powder and 2.5 g of magnesium oxide powder into a ball milling jar, and ball mill using a planetary ball mill. The ball-to-material ratio is 1.2:1, the rotation speed is 150 r / min, the mixing time is 60 min, and the milled powder is passed through a 60-mesh sieve to obtain a mixed powder.
[0071] 2) Place the mixed powder in a heat-insulating structure, and put it together with the heat-insulating structure into a microwave resonator cavity. Turn on the microwave source with a frequency of 2.45 GHz and an output power of 11 kW. Intermittently adjust the input power from low to high. Below 600 °C, the input power uniformly increases by 1 kW every 10 min; after measuring the temperature at 600 °C, increase the input power according to the heating rate to maintain the heating rate at 18 °C / min. When the temperature rises to 1350 °C, keep it warm for 4.5 h, and then turn off the microwave source to obtain magnesium titanate composite powder.
[0072] 3) Add the obtained magnesium titanate composite powder and 5 g of magnesite into a ball milling jar, and ball mill using a planetary ball mill. The ball-to-material ratio is 1.2:1, the rotation speed is 150 r / min, the mixing time is 60 min, and the milled powder is obtained after ball milling.
[0073] 4) After pre-pressing and forming the above mixed powder into a ceramic green body at a pressure of 85 MPa, place the ceramic green body in a heat-insulating structure, and put it together with the heat-insulating structure into a microwave resonator cavity. Turn on the microwave source with a frequency of 9.15 GHz and an output power of 6 kW. Intermittently adjust the input power from low to high. Below 600 °C, the input power uniformly increases by 1 kW every 10 min; after measuring the temperature at 600 °C, increase the input power according to the heating rate to maintain the heating rate at 18 °C / min. When the temperature rises to 1350 °C, keep it warm for 4.5 h, and then turn off the microwave source to obtain magnesium oxide-magnesium titanate composite material.
[0074] Structure Characterization
[0075] Figure 1 XRD pattern of the magnesium oxide-magnesium titanate composite material in Example 1; as Figure 1 shown, the obtained composite material only contains two substances, magnesium oxide and magnesium titanate, and has a high crystallinity.
[0076] Figure 2 SEM image of the magnesium oxide-magnesium titanate composite material in Example 2; as Figure 2 shown, there are annular gaps formed around the large particle aggregates.
[0077] Application Case
[0078] Combine the magnesium oxide-magnesium titanate composite material prepared in Example 1 with a cordierite-mullite substrate by hot pressing sintering (pressure 50 MPa) to form a composite sagger.
[0079] Alkali resistance test: The above-mentioned composite sagger and LiOH (simulating an alkaline environment) were co-fired at 800 °C for 4 h, and the surface erosion depth was measured to be <100 μm, which is better than 300 μm of pure cordierite-mullite, indicating that the magnesium oxide-magnesium titanate composite material of the present invention can improve the alkali resistance of the sagger.
[0080] Thermal shock stability test: The above-mentioned composite sagger was heated to 1100 °C and then subjected to room temperature water quenching cycles. The results showed that there was no cracking after more than 100 cycles, indicating that the sagger made of the magnesium oxide-magnesium titanate composite material of the present invention has excellent thermal shock resistance.
[0081] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a magnesium oxide-magnesium titanate composite material, characterized in that, It includes the following steps: Mix magnesium oxide and titanium oxide by first ball milling, and perform the first microwave heating treatment on the obtained mixed powder to obtain magnesium titanate composite powder; Mix the magnesium titanate composite powder and magnesite by second ball milling to obtain a composite; After pre-pressing and forming the composite into a ceramic green body, perform the second microwave heating treatment to obtain a magnesium oxide - magnesium titanate composite material.
2. The preparation method according to claim 1, characterized in that, The mass ratio of the magnesium oxide, titanium oxide and magnesite is 5 - 10:100 - 150:15 - 20.
3. The preparation method according to claim 1 or 2, characterized in that, The conditions of the first ball milling and mixing include: the ball-to-material ratio is 0.5:1 - 2:1, the rotation speed is 100 - 300 r / min, and the time is 60 - 120 min.
4. The preparation method according to claim 1, characterized in that The frequency of the first microwave heating treatment is 2.45 GHz or 9.15 GHz, and the output power is 2 - 15 kW; the conditions of the first microwave heating treatment include: when the temperature ≤ 600 °C, the power increases by 1 kW every 5 - 10 min; when the temperature > 600 °C, adjust the heating rate to 10 - 20 °C / min, heat up to 1200 - 1400 °C, and the holding time is 3 - 5 h.
5. The preparation method according to claim 1, characterized in that, The conditions of the second ball milling and mixing include: the ball-to-material ratio is 0.5:1 - 2:1, the rotation speed is 100 - 300 r / min, and the time is 60 - 120 min.
6. The preparation method according to claim 1 or 5, characterized in that, The frequency of the second microwave heating treatment is 2.45 GHz or 9.15 GHz, and the output power is 2 - 15 kW.
7. The preparation method according to claim 6, characterized in that, The conditions of the second microwave heating treatment include: when the temperature ≤ 600 °C, the power increases by 1 kW every 5 - 10 min; when the temperature > 600 °C, adjust the heating rate to 10 - 20 °C / min, heat up to 1200 - 1400 °C, and the holding time is 3 - 5 h.
8. The preparation method according to claim 1, wherein Both the first microwave heating treatment and the second microwave heating treatment are carried out in a heat preservation structure; the heat preservation structure includes an alumina hollow sphere layer, a lightweight mullite sheet layer or a lightweight quartz layer, a polycrystalline mullite fiber cotton layer or an alumina fiber layer, and a lightweight mullite sheet layer or a lightweight quartz layer that are sequentially stacked from the inside to the outside.
9. A magnesium oxide - magnesium titanate composite material prepared by the preparation method according to any one of claims 1 - 8.
10. The application of the magnesium oxide-magnesium titanate composite material according to claim 9 in the sintering of the battery cathode material, characterized in that, The magnesium oxide - magnesium titanate composite material is used in combination with a cordierite - mullite crucible base as a working surface.